2021
DOI: 10.2174/1573407215666191120125608
|View full text |Cite
|
Sign up to set email alerts
|

Natural Fused Heterocyclic Flavonoids: Potent Candidates as Anti- Inflammatory and Anti-Allergic Agents in the Treatment of Asthma

Abstract: : In the last two decades, the flavanoids containing fused heterocyclic nucleus in their chemical structure have emerged to display a variety of pharmacological effects including anti-allergic and anti-inflammatory the most recent to the list. These polyphenolic compounds exert their pharmacological effect by various mechanisms including inhibition of human neutrophil elastase, cytokines (Interleukins- IL-3 and IL-4) and mast cells. Quercetin, Pycnogenol, Rutin and Kampferol are the few bio-flavonols out of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Quercetin, kaempferol, luteolin and wogonin are all flavonoids, which have different therapeutic activities, and can act as cardioprotective, antiviral, antidiabetic, anti-inflammatory, antibacterial, and anticancer agents. 34 , 35 Research has showed that quercetin can reduce the production of IL-6, IL-8, IL-1β, and TNF-α, and suppress the activation of NF-κB to achieve an anti-inflammatory effect. 36 Moreover, quercetin possesses anticarcinogenic, antioxidant, free-radical scavenging, antifibrotic, and antiproliferative properties, inhibiting apoptosis and enhancing early innate immunity that can be expressed in different cell types and animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin, kaempferol, luteolin and wogonin are all flavonoids, which have different therapeutic activities, and can act as cardioprotective, antiviral, antidiabetic, anti-inflammatory, antibacterial, and anticancer agents. 34 , 35 Research has showed that quercetin can reduce the production of IL-6, IL-8, IL-1β, and TNF-α, and suppress the activation of NF-κB to achieve an anti-inflammatory effect. 36 Moreover, quercetin possesses anticarcinogenic, antioxidant, free-radical scavenging, antifibrotic, and antiproliferative properties, inhibiting apoptosis and enhancing early innate immunity that can be expressed in different cell types and animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids are the polyphenols associated with the most outstanding research progress in recent years. They mainly affect the secretion process of immune cells, mitosis, and the interaction between cells and significantly influence the inhibition of allergic reactions ( 12 ). Flavonoids inhibit the release of the proteolytic enzyme β-hexosaminidase and histamine from mast cells ( 13 , 14 ).…”
Section: Anti-allergic Effects Of Plant Polyphenolsmentioning
confidence: 99%
“…Structurally, they are composed of two benzene rings, connected by an oxygen-containing heterocycle [86] . Flavonoids have antiallergic, anticancer, antioxidant, antibacterial and antiviral properties, and are widely used as insecticides [87][88][89] to control a variety of insect pests, such as P. xylostella, aphids, locusts and tobacco mosaic virus [90][91][92][93] .…”
Section: Flavonoidsmentioning
confidence: 99%